2020
DOI: 10.7717/peerj.8694
|View full text |Cite
|
Sign up to set email alerts
|

Impact of breast surgery on survival of patients with stage IV breast cancer: a SEER population-based propensity score matching analysis

Abstract: Background Breast surgery for stage IV breast cancer remains controversial. The aim of this study was to investigate the impact of breast surgery on survival of stage IV breast cancer patients based on the Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2015. Methods In total, 13,034 patients were selected and divided into surgery and non-surgery groups. Univariate and multivariable analyses were conducted to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 29 publications
6
13
0
Order By: Relevance
“…In this large cohort, an improved OS was found in the surgery group compared with the non-surgery group even after propensity score matching (HR = 0.68, 95% CI [0.63–0.72], p < 0.001) ( 27 ). The above-mentioned findings are in consistent with the previous studies showing that surgical procedure has a key role in de novo stage IV BC therapy ( 17 , 25 , 26 , 28 , 29 ) as surgery may substantially reduce overall tumor burden and improve survival by activating immune responsiveness ( 30 , 31 ). But other studies held different opinions.…”
Section: Discussionsupporting
confidence: 91%
“…In this large cohort, an improved OS was found in the surgery group compared with the non-surgery group even after propensity score matching (HR = 0.68, 95% CI [0.63–0.72], p < 0.001) ( 27 ). The above-mentioned findings are in consistent with the previous studies showing that surgical procedure has a key role in de novo stage IV BC therapy ( 17 , 25 , 26 , 28 , 29 ) as surgery may substantially reduce overall tumor burden and improve survival by activating immune responsiveness ( 30 , 31 ). But other studies held different opinions.…”
Section: Discussionsupporting
confidence: 91%
“…In this large cohort, an improved OS was found in the surgery group compared with the nonsurgery group even after propensity score matching (HR = 0.68, 95% CI [0.63-0.72], p < 0.001) (27). The above-mentioned findings are in consistent with the previous studies showing that surgical procedure has a key role in de novo stage IV BC therapy (17,25,26,28,29) as surgery may substantially reduce overall tumor burden and improve survival by activating immune responsiveness (30,31). But other studies held different opinions.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study based on the SEER database (1998-2011) suggested a survival benefit with a surgical procedure (median OS, 34 months for surgery vs. 18 months for non-surgery), but the data about HER2 status in this study was incomplete (24). However, other recent studies based on the SEER database (2010-2015), the information about HER2 status was integral, also proposed that surgery could improve OS and BCSS in patients with stage IV BC (25,26). Moreover, one research based on the NCDB database also highlighted that surgery could benefit patients with stage IV BC.…”
Section: Discussionmentioning
confidence: 64%
“…With respect to the survival effects of LRT in patients with dnMBC, retrospective studies have shown the potential survival bene ts [8,15,[39][40][41][42][43][44][45] , while prospective studies have revealed mixed results [29] . Currently, three published prospective studies have assessed the impact of LRT in dnMBC.…”
Section: Discussionmentioning
confidence: 99%
“…The latest research from the NCDB (2003-2012) demonstrated that among women alive 1 year after a diagnosis of metastatic breast cancer, surgical resection of the primary tumor was associated with improved survival, regardless of treatment sequence [8] . Another recent study based on the SEER database (2010-2015) proposed a survival advantage with surgical intervention (median OS, 43 months for surgery vs. 27 months for non-surgery) [45] . Similarly, in our study, the median OS of the two groups was 42 months vs. 22 months, respectively.…”
Section: Discussionmentioning
confidence: 99%